2016
DOI: 10.1186/s12910-016-0139-8
|View full text |Cite
|
Sign up to set email alerts
|

Seeking consent for research with indigenous communities: a systematic review

Abstract: BackgroundWhen conducting research with Indigenous populations consent should be sought from both individual participants and the local community. We aimed to search and summarise the literature about methods for seeking consent for research with Indigenous populations.MethodsA systematic literature search was conducted for articles that describe or evaluate the process of seeking informed consent for research with Indigenous participants. Guidelines for ethical research and for seeking consent with Indigenous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(81 citation statements)
references
References 38 publications
2
67
0
2
Order By: Relevance
“…1 Specific feedback is given on how to communicate in a way that is embraced by remote Aboriginal communities leading to better recruitment rates and more meaningful research outcomes and forming relationships which embody respect for Aboriginal culture.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Specific feedback is given on how to communicate in a way that is embraced by remote Aboriginal communities leading to better recruitment rates and more meaningful research outcomes and forming relationships which embody respect for Aboriginal culture.…”
Section: Resultsmentioning
confidence: 99%
“…Reflections on the consent process and community engagement for research with Indigenous populations are rarely documented as shown in our systematic review. 1 In response, The Picture Talk Project was initiated by leaders of remote Aboriginal communities of the Kimberley to have a 'Yarn' about the research process.…”
Section: Methodsmentioning
confidence: 99%
“…A systematic review of seeking consent in research with indigenous communities (Fitzpatrick et al, ) concluded that ongoing consultation with the indigenous community is required in order to determine how consent can be sought and how the process can be evaluated.…”
Section: Culturementioning
confidence: 99%
“…Customisation is therefore needed to accommodate the cultural dimensions of consenting, recognising the different needs of different patient groups, health practitioners and healthcare environments. As an example, in Aotearoa/New Zealand, there is an explicit need to include a Māori perspective as part of the research and consenting process . The inherent adaptability of e‐content should improve stakeholders’ technical capacity to navigate the inevitable, ongoing tensions between standardisation and customisation (see also Table ) …”
Section: Introductionmentioning
confidence: 99%